Green Economy In The Perspective Of Sustainable Development - Keila Putri Zhafrani; Fahmi Ashari S. Sihaloho (International Journal of Economics, Science, and Education, 2026)
Purpose: The green economy has emerged as a strategic approach to achieving sustainable development by integrating economic growth, environmental sustainability, and social inclusion. As global concerns regarding climate change, environmental degradation, and resource scarcity continue to intensify, governments, businesses, and researchers have increasingly emphasized the importance of transitioning toward a greener economic model. This study aims to systematically review and synthesize the existing literature on the green economy from a sustainable development perspective, focusing on its key concepts, determinants, implementation strategies, and socioeconomic and environmental impacts. Design/Methodology/Approach: This study employs a systematic literature review (SLR) approach by analyzing peer-reviewed journal articles published between 2015 and 2025 and indexed in reputable academic databases, including Scopus, Web of Science, and Google Scholar. The review process follows the PRISMA guidelines to ensure methodological rigor, transparency, and replicability. Relevant articles were selected based on predefined inclusion and exclusion criteria and analyzed using thematic synthesis. Findings: The findings reveal that the green economy is primarily characterized by renewable energy development, green innovation, circular economy practices, sustainable consumption and production, and efficient resource utilization. The literature indicates that government policies, technological advancement, environmental awareness, financial support, and stakeholder collaboration are critical factors influencing the successful implementation of green economy initiatives. Furthermore, green economy practices contribute positively to economic growth, employment generation, environmental protection, carbon emission reduction, and long-term sustainable development. Research Limitations/Implications: This review is limited to selected academic databases and English-language publications, which may affect the comprehensiveness of the findings. Future research is encouraged to conduct empirical studies examining the effectiveness of green economy initiatives in developing countries and across different industrial sectors. Practical Implications: The findings provide valuable insights for policymakers, business leaders, and development practitioners in designing and implementing strategies that support sustainable economic transformation and environmental stewardship. Originality/Value: This study offers a comprehensive synthesis of green economy literature and identifies emerging trends and research gaps that can guide future scholarly investigations and policy development. Paper Type: Literature Review